A Study of Knowledge-level by Some Pests Affecting on Apple Trees and Methods of their Control, for Farmers in Some Regions Shabiat AL Gabal Alaktar - Al.Zobaidy, Dakhel H.; Mohammed, Mohammed A.; Sergiwa, Salah; Abugela, Omran Abusalah (Al-Mukhtar Journal of Sciences, 2001)
The main objective of this research is to study the knowledge-level of farmers by four dominant types of pests (ZEUZERA PYRIN, ERIOSOMA LANGERA, and TETRANYCHUS URITICA (KOCH) CYDIA (CARPOCASA) POMONELLA. Affecting on apple trees and their methods of control. Data have been collected by questionnaire and personal interview from (140) farmers representing the sample of this research in five regions (Al waseita, Shahhat, Gernada, Massa, and Omar Al moukhtar). The results showed a low knowledge-level for farmers by apple treel-training and control of these pests. The researchers recommended the associated authorities interesting in development and developing of agriculture to follow up national program curriculum and curriculum and to activate the extension role to protect the national production.